Revitalization of religious education based on dialogue, tolerance and harmony of religious people in Indonesia - Ichsan, Yazida; Sirait, Sangkot; Arif , Mahmud (Universitas Ahmad Dahlan, 2024)
From a sociological perspective, religion is considered to have a dual function. On the one hand, it is constructive by embodying the values of love and peace. On the other hand, it is destructive which results in massive damage. One of the efforts to overcome conflicts between multi-religious communities is the effort of dialogue, mitsaq and tolerance. Islamic religious education is one of the mediums in realizing this aspect. By internalizing the awareness of plurality, dialogue efforts by seeking universal religious values, explaining the concept of mitsaq and internalizing the values of tolerance in education, reconciliation efforts against religious conflicts are expected to run effectively so that harmony between religious communities in Indonesia is realized.